Difficult-to-treat asthma: The pitfalls of comorbidity I. Extrinsic allergic alveolitis - Pałczyński, Cezary; Kupryś-Lipińska, Izabela; Łacwik, Piotr; Kuna, Piotr (Lekarz POZ, 2017)
Asthma is one of the most common noncommunicable disorders, affecting over 300 million people globally. While the majority of patients are able to achieve satisfactory disease control using the currently available treatment options, around 5-10% of asthmatics remain difficult to treat. It is caused by many different factors, such as undiagnosed comorbidities, as well as the occurrence of disorders with clinical manifestations similar to those found in asthma. Extrinsic allergic alveolitis (EAA, also: hypersensitivity pneumonitis) is an example of such a diagnostic challenge. The major clinical features of EAA, which often lead to its underdiagnosis or misdiagnosis, include pulmonary wheezes and airflow obstruction found on spirometry. Moreover, asthma and EAA can coexist in one patient. An early diagnosis of hypersensitivity pulmonitis is of crucial importance because the acute and subacute forms are potentially reversible if treated early in the course of disease.